2021
DOI: 10.51629/ijeamal.v2i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organizational Support and Employee Performance

Abstract: The employee’s in-role and extra-role performance has badly effected due to prevalence of COVID-19. The aim of the study is to examine the relationship of perceived organizational support and employee performance. The role of organizational justice is examined as a moderator. A sample of 222 bank employees was selected on convenience basis.  The responses were recorded through closed ended questionnaires. The responses were analyzed through Partial Least Square Structural Equation Modeling Method. In times of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Furthermore, GPOS perceptions of employees urge them to facilitate their employer in achieving different environmental objectives. Shabbir, et al [66] believed that the GPOS of an organization helps its employees in developing positive feelings to think that their environmentally friendly act will be rewarded by their employer. Shoss, et al [67] regarded POS as a critical factor that motivates employees to show a great commitment to overall organizational success.…”
Section: H3mentioning
confidence: 99%
“…Furthermore, GPOS perceptions of employees urge them to facilitate their employer in achieving different environmental objectives. Shabbir, et al [66] believed that the GPOS of an organization helps its employees in developing positive feelings to think that their environmentally friendly act will be rewarded by their employer. Shoss, et al [67] regarded POS as a critical factor that motivates employees to show a great commitment to overall organizational success.…”
Section: H3mentioning
confidence: 99%
“…Cunha & Marques (2022) stated that personal factors, including organizational support, can have a positive impact on the innovation outcomes and innovative behavior of nurses during the Covid-19 pandemic. Another similar study is the study by Shabbir et al (2021) which states that good organizational support, together with organizational justice, will result in good work performance for bank employees during the Covid-19 pandemic. Zhang et al (2022) also found that organizational support is related to job performance, as perceived organizational support would lessen the chance of role overload and thus will increase job engagement that, attenuate job performance.…”
Section: Discussionmentioning
confidence: 96%
“…In additional, the psychological mechanism of employees’ perception of their organization’s loyalty (commitment) is related to the concept of social exchange and a psychological contract between employees and their organization ( Garcia et al, 2021 ). POS is capable of affecting employees’ work attitude and behavior through the effort-anticipated reward association and the reinforcement of personal social emotional need ( Shabbir et al, 2021 ). Consequently, organizations can use employees’ POS to boost their OCB.…”
Section: Conceptual Frameworkmentioning
confidence: 99%